Study on the temperature characteristics caused by two fires in a tunnel based on multi-layer zone model. (May 2023) - Jia, You; Fan, Xueliang; Deng, Yelin; Zhu, Xinlei; Yu, Qingyang; Zhao, Weifeng
Graphical abstract: Highlights: The temperature characteristics induced by two fires in a tunnel is investigated. The multi-layer zone model is improved for two fires and parameters. The model is verified by both experiments and simulations. Abstract: Temperature characteristics induced by two pool fires in a tunnel are studied in this paper. Multi-layer zone (MLZ) model, small-scale experiments, and fire dynamics simulations are carried out considering different fire sizes and spacing. The multi-layer zone model is used for two fires in a tunnel and verified by experiments and simulations. The results show that the effect of different numbers of vertical divisions ( N  ≥ 5, where N is number of vertical divisions) can be ignored, while the radiation between layers is an integral part of the model. Moreover, the calculated results of the revised model have good agreement with experiments and numerical simulations. Therefore, the improved model can reasonably predict maximum, longitudinal, and vertical temperature characteristics.